Tribology and surface topography of Al-10Cu-Fe alloy produced by rheocasting process - Sankara Rao L.; Jha A.K.; Ojha S.N. (My University, 2025)
In the present investigation, Al-10Cu-Fe alloys were produced by rheocasting process at different mechanical stirring speeds. These castings were poured into a metallic mould at a temperature of 620 °C i.e. in the semi-solid state. The resultant microstructures and wear properties were compared with a conventional metal mould cast alloy. The rheocast alloys have shown better mechanical (ultimate tensile strength and hardness) and wear properties as compared to metal mould cast alloy. Moreover, rheocast alloy which was produced at 1200 rpm stirring speed exhibited enhanced wear and mechanical properties as compared to other rheocast alloys. The improved wear rate for this alloy may be attributed to finer grain size and the nearly-spherical morphology of the primary α-phase. The metal mould cast and rheocast alloy at 400 rpm have shown adhesive wear. Whereas, other rheocast alloys have displayed microcutting abrasion. The noticeable decrease in the average roughness for 3 m s-1 sliding velocity was observed as compared to the 1 m s-1. In addition, the average roughness value of the 1200 rpm stirred alloy is lower than that of the alloy produced at 800 rpm stirring speed. © 2017 IOP Publishing Ltd.